How Middle Eastern is Israel? (KULT_online, 2014)
Israeli Identity: Between Orient and Occident is an important book on contemporary Israeli identities and Israeli discourses on the East and the West. The authors examine various aspects of Israeli social, political, and cultural life, challenging a common belief that Israel is a Western state that only geographically is located in the Middle East. The contributors explore various manifestations of Israeli identities in a quest to answer an old, but lingering question: how Middle Eastern are Israel and the Israelis?